Just a Few Miles South : Timeless Recipes from Our Favorite Places. - Michel, Ouita (University Press of Kentucky, 2021)
"For twenty years, diners in the Bluegrass have been able to whet their appetite for Ouita Michel's sustainable, farm-to-table cuisine at one of her many acclaimed restaurants. Each restaurant-from Wallace Station to Holly Hill Inn-features dishes that combine Kentucky's bounty with Michel's celebrated vision. Diners can enjoy traditional southern staples like buttermilk biscuits, country ham, and po boy sandwiches, or opt for unique variations on international favorites and American classics. Now, readers around the country can experience what makes Ouita Michel a culinary and cultural treasure. Just a Few Miles South serves up the recipes that patrons of Michel's restaurants have come to know and love, including the Bluegrass Benedict breakfast sandwich, Ouita's Sardou Panini, Wallace Station's Creamy Chicken and Mushroom Soup, and Honeywood's Hoecake Burger. Some dishes offer creative twists on classics, like the Inside Out Hot Brown, the Wallace Cubano, or the Bourbon Banh Mi. Throughout, the chefs responsible for these delicious creations share the rich traditions and stories behind the recipes. When you can't get down to your favorite place, this book will help you bring home the aroma, the flavors, and the love of fresh foods made with locally sourced ingredients-and share it all with friends and family"-- Provided by publisher.
Description based upon print version of record.
Part 6: Soups, Stews, and Salads.
Keywords: Cooking, American -- Southern style.; Cooking -- Southern States.; Cuisine américaine du Sud.; COOKING / Regional & Ethnic / American / Southern States; Cooking; Cooking, American -- Southern style; Southern States; Electronic books.